The application of transformations of the gravity and magnetic field using averaging method for determination and interpretation of low-amplitude anomalies - Грищук, П.; Булах, Є.; Нурмухамедов, В. (Київський національний університет імені Тараса Шевченка, 2006)
Formulas and graphs of basic component of the potential field for 2-D model with the vertical section – rectangular cell are resulted. The theory of transformation and interpretation of the fields is resulted by the method of comparison due to averaging. The examples of interpretation of the real anomalies and its comparison with drilling data are presented.

Приведено формули та графіки основних компонент потенціального поля для двомірної моделі з вертикальним перерізом – прямокутна комірка. Наведено теорію трансформації та інтерпретації полів методом порівняння за допомогою осереднення. Представлено приклади інтерпретації реальних аномалій та їх співставлення з даними буріння.
Застосування трансформацій гравімагнітного поля способом осереднення при виділенні та інтерпретації малоамплітудних аномалій